ANALYSIS AND DESIGN CASH SALES ACCOUNTING INFORMATION SYSTEM AT UTAMA ALUMINIUM STORES - Azhelia Syafira; Lana Sularto (Jurnal Ilmiah Ekonomi Bisnis, 2019)
This research was conducted at Utama Aluminum Store which is a companyengaged in general trading or general supplier and manufacture of various doors, frames, windows, X Panda, mosquito wire, and window displays. The purpose of this study was to determine and evaluate the cash sales accounting information system that was running at Utama Aluminum Store and to provide an alternative design of cash sales accounting information systems at Utama Aluminum Store. The data used in this study are primary data obtained directly from Utama Aluminum Store and secondary data obtained in the form that has been in the form of publications. The analytical tool used in this study is a qualitative descriptive analysis tool by analyzing the system using the COSO method, which then continues the conceptual design phase by designing a document flow chart (flowchart), Data Flow Diagram (DFD), Entity Relationship Diagram (ERD), Normalization. After that proceed to the physical design stage but only limited to designing database design, input and output design. Based on the results of the study, the researchers found that the cash sales system run by the company was less effective because there were still a number of tasks in the sales section, and the warehouse section, and also the documents used were still not meeting the system requirements. In addition, the resulting report is a sales report that is only recorded in a book that can cause the resulting report to be ineffective and cause fraud. Furthermore, the researchers designed a cash sales accounting information system that is able to overcome these weaknesses and shortcomings.